Hubungan Servant Leadership dengan Quality of Work Life (QWL) pada Karyawan X di Jakarta - Hasri, Ni Komang Widi Krisna; Merdiaty, Netty (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study explains the relationship between servant leadership and the quality of work life of X employees in Jakarta, which is a private financial services company. This study aims to determine whether there is a relationship between servant leadership and quality of work life using 113 respondents from company X. The method used in this study is quantitative correlational analysis with the aim of seeing the relationship between the two variables studied, which in the process of data analysis using the help of IBM SPSS 25 software. The results in this study showed a value of correlation coefficient spearman’s of 0.772 or p < 0.05. This value explains that servant leadership with quality of work life has a positive relationship. Based on the results of research that shows that there is a relationship between servant leadership and the quality of work life in employee X.